210 Effects of D‐methionine compared with L-methionine on N retention, gut morphology and antioxidant status of weaned pigs. (30th November 2020) - Htoo, John K; Mathai, John; Blavi, Laia; Liu, Yanhong; González-Vega, Caroline; Stein, Hans H
Abstract: A N-balance study was conducted to compare the effect of D-methionine (D-Met) or L-methionine (L-Met) supplementation on N balance, gut morphology and antioxidant status of weaned pigs. Fifty-six weaned barrows (10.5 ± 1.2 kg initial BW) were allotted to 7 diets in 2 blocks. A Met-deficient basal diet (BD; 0.24% standardized ileal digestible (SID) Met) but adequate in other AA, was supplemented with 3 graded levels (0.036, 0.072, and 0.108%) of D-Met or L-Met. After a 7-d adaptation, feces and urine were collected quantitatively for 5 d to determine N balance. At the completion of the experiment, blood samples were collected from all pigs. Pigs fed the BD and pigs fed the highest level of SID Met (0.34%) of both Met sources were euthanized and tissue samples from liver, kidney, muscle (longissimus dorsi), duodenal and jejunal mucosa were collected. N retention as % of N intake increased (P < 0.001; 67, 72, 73, 74, 71, 74, 74%, respectively) by graded supplemental level of D-Met or L-Met. However, there was no interaction between Met source and supplemental level for all N-balance metrics. Using a slope-ratio regression, the bioavailability of D-Met relative to L-Met was 100.1% (95% confidence intervals: 85-116%) based on N retention (% of N intake). Villus height and crypt depth in the duodenum and jejunum were not affected by Met sources. Pigs fed the D-Met diet had a greater (P < 0.05) total glutathione concentration in liver (4.9 vs. 1.5 µM) vs. BD. However, total antioxidant capacity and concentration of thiobarbituric acid-reactive substances in liver, muscle or plasma samples were not different among treatments. Supplementation with D-Met increased glutathione peroxidase activity in kidney (878 vs. 413 and 229 mU/mL; P < 0.05) compared with BD or L-Met diet, however, activity of glutathione reductase in liver and kidney were not affected by treatments. These data indicate that D-Met and L-Met are equally efficient to support N retention, intestinal morphology and oxidative status in weaned pigs.